Shaping and Locomotion of Soft Robots Using Filament Actuators Made from Liquid Crystal Elastomer–Carbon Nanotube Composites. (17th June 2020) - Liu, Jiaqi; Gao, Yuchong; Wang, Haihuan; Poling-Skutvik, Ryan; Osuji, Chinedum O.; Yang, Shu
Abstract : Muscle‐Like Soft Robots In article number 1900163, Shu Yang and co‐workers demonstrate soft robots capable of locomotion and shape transformation using muscle‐like soft actuators made from liquid crystal elastomers, carbon nanotubes and cellulose nanocrystals. The soft robots exhibit reversible infrared light and electrothermal responsiveness with dexterity, high mechanical strength, and fast actuation speed.